Hubungan Tinggi Badan terhadap Fungsional Bahu pada Pitcher Baseball di Bali - Januardha Valerio Itta; I Gede Eka Juli Prasana; Ni Luh Nopi Andayani; Anak Agung Gede Angga Puspa Negara (KOLONI, 2026)
Baseball pitchers are overhead athletes at high risk of shoulder dysfunction due to repetitive pitching movements with high biomechanical loads. Height can help increase a pitcher's throwing velocity but is also thought to contribute to increased mechanical loads on the shoulder during pitching through increased arm length, stride length, and shoulder torque. However, the relationship between height and shoulder function in baseball pitchers remains unclear. This study aimed to determine the relationship between height and shoulder function in baseball pitchers in Bali. The study used a cross-sectional design with 100 baseball pitchers aged 15–25 years selected by purposive sampling. Height was measured using a stadiometer, while shoulder function was measured using the Kerlan-Jobe Orthopedic Clinic (KJOC) Score questionnaire. Statistical analysis used the Spearman's rho bivariate test. A significant negative relationship was found between height and KJOC score (r=-0.119 and p=0.240). These findings indicate that height has no significant relationship to shoulder function in baseball pitchers in Bali. Shoulder function is thought to be more influenced by other factors such as pitching biomechanics, neuromuscular control, muscle strength, and adaptation to repetitive pitching activity.